International business cycles and financial frictions - Wen Yao (Bank of Canada, 2012)
This paper builds a two-country DSGE model to study the quantitative impact of financial frictions on business cycle co-movements when investors have foreign asset exposure. The investor in each country holds capital in both countries and faces a leverage constraint on her debt. I show quantitatively that financial frictions along with foreign asset exposure give rise to a multiplier effect that amplifies the transmission of shocks between countries. The key mechanism is that a negative shock in the home country reduces the wealth of investors in both countries, which tightens their leverage constraints, leading to a fall in investment, consumption, and hours worked in the foreign country. Compared to the existing literature, which tends to produce either negative or positive but small cross-country correlations, this model produces positive and sizable correlations that are consistent with the data. The model can account for most of the investment, employment and consumption correlations and predicts more than half of the output correlation. In addition, the model shows that, consistent with empirical findings, when investors have more foreign asset exposure to the other country, the output correlation between the two countries increases.
Keywords: E30; F42; F44; 330; Business fluctuations and cycles; International financial markets; International topics